MRI Changes in the Brain: A Key to the Diagnosis of Wilson’s Disease - Iftikhar, Shehla; Qasmi, Imran Masoud; Dildar, Nazia; Aamir, Umar; Saleem, Fahad (Journal of Pharmacy Practice and Community Medicine)
A 10 year old boy was presented with weakness of upper and lower limbs and generalized body aches for the last three months. Later he developed mild uncoordinated movements, ataxia, slurred speech and dysarthria. MRI of the brain was advised that showed bilateral T2W hyperintensity in caudate, lentiform nuclei and pons. Ophthalmological examination showed Kayser Fleisher rings. 24 h urinary copper levels established the diagnosis of Wilson’s disease.
Keywords: MRI changes; Brain; Diagnosis; Wilson's disease